Analisis Ijtihad ʻAbdullah Bin ʻAbbās pada Masalah ‘Aul dan Radd dalam Fikih Mawārīṡ - Suleha Suleha; Rahmat Rahmat; Irsyad Rafi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The aim of this research is to analyze the ijtihad (jurisprudential reasoning) of ʻAbdullah bin ʻAbbās regarding the issues of ‘Aul and Radd within the context of Islamic inheritance law (fikih mawāriṡ). This study employs a literature review method (library research) with a normative juridical approach, seeking legal sources through evidence from the Qur’an, the sayings of the Prophet Muhammad (hadith), and the opinions of scholars. The findings of the research indicate that the concept of ‘Aul serves as a mechanism to adjust inheritance portions when the total specified in the Qur’anic verses exceeds the actual available estate. On the other hand, the concept of Radd involves distributing the surplus of the estate to specific heirs after the primary distribution. ʻAbdullah bin ʻAbbās's ijtihad rejects the application of ‘Aul, arguing that adjusting inheritance portions is unnecessary based on his interpretation of Qur’anic verses. Regarding Radd, he opines that the surplus should not be given to spouses and grandmothers due to kinship reasons. His stance against ‘Aul does not guarantee fairness in inheritance distribution, a fundamental principle in Islamic law, unlike Radd which ensures a fair distribution and upholds the rights of specified heirs as prescribed by Shariah. Excluding grandmothers from receiving Radd inheritance is seen as inadequate in considering the principles of justice and balance in Islamic inheritance law, as grandmothers are among the heirs of aṣḥāb al-furūḍ through familial ties, distinct from spouses who inherit through marital relations. This research aims to contribute to the advancement of knowledge in the field of Islamic inheritance law (Fikih Mawārīṡ) and serve as a reference for future studies.